1992
DOI: 10.1029/91wr02852
|View full text |Cite
|
Sign up to set email alerts
|

Estimating urban residential water demand: Effects of price structure, conservation, and education

Abstract: Water demand equations are estimated using the most current American Water Works Association (1984) survey of 430 (of 600 largest) U.S. utilities. The data set was augmented by monthly rainfall and temperature data from the National Oceanic and Atmospheric Administration's climatological data. Demographic data were obtained from the U.S. Department of Commerce (1988). Besides the usual endogeneity problems involving block price structures this paper also examines the possible endogeneity of conservation and ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
132
1
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(138 citation statements)
references
References 25 publications
3
132
1
2
Order By: Relevance
“…Per capita water use in U.S. cities has been declining steadily over the past few decades [Rockaway et al, 2011] and not only in areas that experience water stress. Nieswiadomy [1992] examined water prices across U.S. cities and found that price elasticity tended to be higher in the South and West, suggesting that climate has some impact on how water is valued. Nevertheless, he found that a water conservation metric did not appear to be related to water use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Per capita water use in U.S. cities has been declining steadily over the past few decades [Rockaway et al, 2011] and not only in areas that experience water stress. Nieswiadomy [1992] examined water prices across U.S. cities and found that price elasticity tended to be higher in the South and West, suggesting that climate has some impact on how water is valued. Nevertheless, he found that a water conservation metric did not appear to be related to water use.…”
Section: Discussionmentioning
confidence: 99%
“…Water prices have been shown to affect demand and are thus a lever for conservation policy [Martin and Kulakowski, 1991;Mercer and Morgan, 1985;Nieswiadomy, 1992;Piper, 2003]. Comparisons between command and control policies versus pricing or incentives have also been explored [Burness et al, 2005].…”
Section: 1002/2015wr016943mentioning
confidence: 99%
“…Several studies of the residential demand for water involved multiple models that differed by region, by functional form, by estimation method, or by which variables were included. Our analysis includes only studies that provided an estimate of the price elasticity of demand and excludes two models that estimated a nonnegative price elasticity of demand [from Nieswiadomy, 1992 …”
Section: Datamentioning
confidence: 99%
“…However, there is no general consensus on a methodology for studying the impact of consumer education and information policies. These policies are widely used by the water industry for controlling water demand, with generally positive results [20,21].…”
Section: Residential Water Demand Related To Social Aspectsmentioning
confidence: 99%